Hepatitis C virus double‐stranded RNA is the predominant form in human liver and in interferon‐treated cells. Issue 2 (10th November 2016) - Klepper, Arielle; Eng, Francis J.; Doyle, Erin H.; El‐Shamy, Ahmed; Rahman, Adeeb H.; Fiel, M. Isabel; Avino, Gonzalo Carrasco; Lee, Moonju; Ye, Fei; Roayaie, Sasan; Bansal, Meena B.; MacDonald, Margaret R.; et al.
Abstract : Hepatitis C virus (HCV) is unique among RNA viruses in its ability to establish chronic infection in the majority of exposed adults. HCV persists in the liver despite interferon (IFN)‐stimulated gene (ISG) induction; robust induction actually predicts treatment failure and viral persistence. It is unclear which forms of HCV RNA are associated with ISG induction and IFN resistance during natural infections. To thoroughly delineate HCV RNA populations, we developed conditions that fully separate the strands of long double‐stranded RNA (dsRNA) and allow the released RNAs to be quantified in reverse transcription/polymerase chain reaction assays. These methods revealed that dsRNA, a pathogen‐associated molecular pattern (PAMP), comprised 52% (standard deviation, 28%) of the HCV RNA in the livers of patients with chronic infection. HCV dsRNA was proportionally higher in patients with the unfavorable IL28B TT (rs12979860) genotype. Higher ratios of HCV double‐stranded to single‐stranded RNA (ssRNA) correlated positively with ISG induction. In Huh‐7.5 cells, IFN treatment increased the total amount of HCV dsRNA through a process that required de novo viral RNA synthesis and shifted the ratio of viral dsRNA/ssRNA in favor of dsRNA. This shift was blocked by ribavirin (RBV), an antiviral drug that reduces relapse in HCV patients. Northern blotting established that HCV dsRNA contained genome‐length minus strands. Conclusion : HCV dsRNA is the predominant form in the HCV‐infected liver and has features of both a PAMP and a genomic reservoir. Interferon treatment increased rather than decreased HCV dsRNA. This unexpected finding suggests that HCV produces dsRNA in response to IFN, potentially to antagonize antiviral defenses. (Hepatology 2017;66:357–370).